EFEKTIVITAS BMP EKMA4215 DALAM MENINGKATKAN PEMAHAMAN MAHASISWA PADA PROGRAM PJJ UNIVERSITAS TERBUKA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the effectiveness of the Buku Materi Pokok (BMP) EKMA4315 Cost Accounting in improving students’ conceptual understanding and application of cost accounting within the distance learning system of Universitas Terbuka. A quantitative descriptive method was employed involving 350 students enrolled in the EKMA4315 course. Data were collected through comprehension tests and a Likert-scale questionnaire assessing the effectiveness of the BMP. Validity testing confirmed 23 out of 25 test items as valid, while reliability testing produced a Cronbach’s Alpha value of 0.876, indicating strong internal consistency. The results revealed a significant improvement in students’ scores, from a mean of 55.40 (pre-test) to 78.50 (post-test), supported by the paired sample t-test (t = 38.72; p < 0.000). The N-Gain value of 0.52 reflected a moderate level of effectiveness, and the reduction in score variability demonstrated more equitable learning outcomes. Regression analysis showed that 57.2 percent of the variance in post-test scores was explained by pre-test performance. Students’ perceptions toward the BMP were positive, with an overall mean score of 4.10. The study concludes that BMP EKMA4315 is effective in supporting independent learning within a distance education context. Recommendations include enhancing content quality and case-based materials, integrating interactive digital features, and strengthening tutorial support to further optimize learning outcomes.